2016
DOI: 10.1177/1358863x15624026
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery disease and abdominal aortic aneurysm growth

Abstract: To determine whether coronary artery disease (CAD) is associated with abdominal aortic aneurysm (AAA) growth, we performed a meta-analysis of currently available studies. Databases including MEDLINE and EMBASE were searched through October 2015 using PubMed and OVID. Search terms included enlargement, expansion, growth, or progression; rate or rates; and abdominal aortic aneurysm. Studies considered for inclusion met the following criteria: the design was unrestricted; the study population was AAA patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…A recent meta-analysis by Li et al 2 of 10 epidemiological studies also showed that CAD was a risk factor for AAA (OR, 1.82; 95% CI, 1.65 to 2.00). Another recent meta-analysis 20 of 20 studies, however, demonstrated a statistically significant association of CAD with slower AAA growth rates (SMD, −0.06; 95% CI, −0.12 to −0.0027; p = 0.04).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A recent meta-analysis by Li et al 2 of 10 epidemiological studies also showed that CAD was a risk factor for AAA (OR, 1.82; 95% CI, 1.65 to 2.00). Another recent meta-analysis 20 of 20 studies, however, demonstrated a statistically significant association of CAD with slower AAA growth rates (SMD, −0.06; 95% CI, −0.12 to −0.0027; p = 0.04).…”
Section: Discussionmentioning
confidence: 94%
“…Although CAD is positively associated with AAA presence, 1,2 it is negatively associated with AAA growth. 20 A previous meta-analysis by Cornuz et al 1 of six population-based risk factor studies of AAA showed that a history of myocardial infarction was a major risk factor or risk indicator for screening-detected AAA (OR, 2.30; 95% CI, 1.92 to 2.75). A recent meta-analysis by Li et al 2 of 10 epidemiological studies also showed that CAD was a risk factor for AAA (OR, 1.82; 95% CI, 1.65 to 2.00).…”
Section: Discussionmentioning
confidence: 99%
“…Even patients without any prior history of cardiac revascularization had significant lesions (found in 2 of every 5 subjects), and those already after PCI had significant lesions in as much as 4 in every 5 patients. It is still unclear whether this high association between the presence of AAA and atherosclerosis is causal or simply due to shared risk factors, as well as which risk factors contribute most to this phenomenon [8,26,27]. Coronary revascularization is an established method of reducing cardiovascular events, but interestingly, a randomized trial carried out in patients undergoing major vascular surgery failed to demonstrate the benefits of prophylactic CAD treatment for the clinical outcomes in patients with angiographically determined coronary artery stenosis [17,28].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between different diabetes treatments and AAA growth above or below the median value was examined using logistic regression. Three regression models were developed for cohorts 1 and 2: model 1 was unadjusted; model 2 was adjusted for risk factors consistently associated with AAA growth (initial AAA diameter, smoking history and ischaemic heart disease); model 3 was adjusted for risk factors or medications identified as being associated with median AAA growth in the univariable analyses ( P < 0·050) as well as those included in model 2. Owing to the small sample size in cohort 3, only models 1 and 2 were used.…”
Section: Methodsmentioning
confidence: 99%